Simulating Bleaching: Long-Term Adaptation to the Dark Reveals Phenotypic Plasticity of the Mediterranean Sea Coral Oculina patagonica - Zaquin, Tal; Zaslansky, Paul; Pinkas, Iddo; Mass, Tali (Frontiers in Marine Science, 2019)
The Eastern Mediterranean Sea scleractinian Oculina patagonica, demonstrates high resilience to repeated seasonal bleaching events, a trait potentially allowing the species to survive through a radically changing climate. However, the physiological and morphological contributors that make this plasticity of O. patagonica possible are poorly understood. Here we use a long-term in-vitro induced bleaching experiment where colonies were reared in a dark environment to examine how O. patagonica colonies can survive without endosymbionts. We assessed the physiological, morphological and genetic adaptations that accompany our controlled bleaching. Measurements reveal changes to respiration and calcification rates both at three and twelve months following the initiation of the darkness experiment, coupled with corresponding macromorphology traits. Upon placing in the dark environment, O. patagonica begins the bleaching process while demonstrating acclimation in which the coral appears to divert its energy to survival resulting in the expulsion of the Symbiodinium population. In addition, the coenosarc exhibits degradation where the coral transforms from a colonial living to a solitary one. Once bleached, we observe adaptation by the solitary polyps characterized by a lower respiration rate yet, regaining their calcification activity and are continuing gametogenesis. However, under bleaching conditions, the newly formed skeletons differ substantially from non-bleached colonies, clearly suggesting an environmental influence on the skeleton morphology. Overall, our study reveals that O. patagonica shows phenotypic plasticity allowing the species to withstand losing their beneficial endosymbionts so as to prosper as a solitary coral. The mechanisms used by this highly resilient coral may provide clues to what corals may require to be able to adapt to life without photosynthetic symbionts.